Pengaruh digital content marketing terhadap purchase intention produk skincare lokal dengan customer loyalty sebagai variabel mediasi - Ambarita, May Hotma Dewi Manik; Tunjungsari, Hetty Karunia (Jurnal Manajemen Bisnis dan Kewirausahaan, 2025)
This study explores the influence of Digital Content Marketing (DCM) on Purchase Intention in the context of local skincare brands in Indonesia. Customer Loyalty is examined as a mediating variable to understand how digital content affects consumer behavior. Data were collected from 220 Instagram users who had engaged with local skincare content and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results show that DCM significantly affects both customer loyalty and purchase intention. Furthermore, customer loyalty is proven to mediate the relationship between DCM and purchase intention. These findings support the Stimulus–Organism–Response (S-O-R) theory and emphasize the role of digital content in shaping consumer engagement and buying intention. This study contributes to digital marketing literature and offers strategic insight for local skincare brands in designing impactful content.